Biochemical comparison of venoms from young Colombian Crotalus durissus cumanensis and their parents - Céspedes,N (2010)
Crotalus durissus cumanensis, a rattlesnake endemic to Colombia and Venezuela, is considered one of the most lethal snake species in Latin America. The aim of the present study was to compare the protein content and biological activity of the venom obtained from eight specimens of C. durissus cumanensis, namely two adults from different localities of Colombia and six offspring born in captivity. Protein profiles of crude venoms were analyzed by SDS-PAGE and RP-HPLC, and biological activities were evaluated for lethality, edema, defibrination, hemolytic and coagulant activities to assess individual venoms of adults and a pool of young snake venoms. Transient edema appeared rapidly after venom inoculation, whereas hemorrhagic effect was not observed. Differences in protein profiles, lethality, hemolytic, coagulant and defibrinating activities between both adult snake venoms were observed; those from the mother snake exhibited higher activities. Venoms from young snakes were similar to the one obtained from the mother, but the coagulant effect was stronger in offspring venoms. Notably, biological effects of the father snake venom were not comparable to those previously described for C. durissus cumanensis from Venezuela and C. durissus terrificus from Brazil, confirming the high variability of the venom from Crotalus species.